Conservative management of giant omphalocele: 20-year experience from a tertiary care center in North India - Kamal Nain Rattan; Jasbir Singh; Poonam Dalal; Ravi Rohilla (Hygeia Press di Corridori Marinella, 2019)
Despite significant advances, the management of giant omphalocele (GO) still remains a challenging job for neonatologists and pediatric surgeons. Early surgical treatment of GO may not be undertaken in every patient due to the risk of fatal hemodynamic and respiratory compromise and associated congenital malformations. We analyzed the profile and outcome of patients with GO who were managed conservatively using povidone-iodine as escharotic agent. A total of 27 neonates with GO were managed conservatively during the study interval (1998-2016). Mean gestational age among survivors and expired group was 37.5 ± 1.5 weeks and 35.0 ± 1.0 weeks, respectively. Mean birth weight was 2,950 ± 500 g in the survivor group and 2,300 ± 450 g in the expired group. Prenatal diagnosis was available in eight patients (29.6%). Twenty-three (85.2%) neonates were born with vaginal delivery. Associated congenital malformations were present in 37% (10/27) patients. The mean duration of complete epithelialization of sac was 10.0 ± 2.5 weeks. Surgical intervention was done at 4-9 months of age. Eight (29.6%) patients expired during the study period. We observed prematurity, low birth weight, associated congenital anomalies and sepsis as risk factors associated with increased mortality.